Une démarche originale de gestion concertée pour préserver la quiétude de la faune sauvage: Biodiv’sports de montagne - Clémence Perrin-Malterre (VertigO)
The increase of practice of outdoor sports, especially in mountain areas, could impact emblematic wildlife of these territories. Collaborative management approaches are developed in order to offer a sharing of space, so that everyone can enjoy the natural environment, while preserving it. This is particularly the case of the Biodiv'sports of mountain approach. The aim of this article is to analyse the construction of agreements and compromises between the different stakeholders (sportsmen, naturalists and protected areas’ managers) involved in this process. Based on the theory of justification, we show the arguments developed by the stakeholders about the legitimate uses of nature, as well as the equivalence principles underlying the compromise between the stakeholders. This compromise involves new relationships between the stakeholders. This process results in management "as a common" of the natural area.